THE EFFECTIVENESS OF TELE-NURSING IN IMPROVING THE QUALITY OF LIFE FOR CHRONIC DISEASE PATIENTS IN REMOTE AREAS - Sulistyo Andarmoyo; Ethan Tan; Dina Carolina Hapsari (Yayasan Adra Karima Hubbi, 2026)
Chronic diseases are a significant burden on healthcare systems, especially in remote areas where access to healthcare is limited. Tele-nursing, an emerging solution involving remote nursing care, has the potential to improve patient outcomes by providing continuous monitoring and support. This study aims to evaluate the effectiveness of tele-nursing in improving the quality of life for chronic disease patients in rural settings. A mixed-methods approach was utilized, incorporating quantitative assessments of patient quality of life through the WHOQOL-BREF questionnaire and qualitative interviews with patients and healthcare providers. Results indicated that patients who received tele-nursing interventions showed a 20% improvement in overall health outcomes and a 25% increase in engagement compared to those receiving traditional care. Additionally, patients reported enhanced satisfaction with their care, feeling more connected to their healthcare providers and empowered to manage their conditions. The study concludes that tele-nursing is an effective tool in improving the quality of life for chronic disease patients in remote areas by providing personalized, accessible care. It highlights the need for further research to explore the long-term sustainability of tele-nursing and its integration into healthcare systems globally.